FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEPUASAN PASIEN TUBERKULOSIS DI RUMAH SAKIT TK II PUTRI HIJAU MEDAN TAHUN 2017 - SUZAN NOVILIA (LP2MTBM MAKARIOZ, 2019)
Tuberculosis is an infectious disease caused by the bacterium Mycobacterium tuberculosis which often infects the lungs. Pulmonary tuberculosis is transmitted from person to person through a droplet that comes out of a pit that comes from the lungs of tuberculosis sufferers. This study aims to determine the factors associated with satisfaction of Tuberculosis patients in Rumkit Tkll Putri Hijau Medan in 2017. This type of research is observational analytic using cross sectional design. The study population was all patients with tuberculosis in Rumkit Tk ll Putri Hijau Medan in 2017. The research sample of 100 people. In this study, primary data with questionnaires and secondary data through medical ricord is required for the Putri Hijau Medan Kindergarten Medan 2017. The data analysis used is univariate analysis with the frequency distribution of research variables, bivariate with chi-square test, and multivariate with logistic regression test. The results showed that there was no gender relationship with satisfaction of tuberculosis patients (p = 0.575), there was no relationship of education with satisfaction of tuberculosis patients (0.744), there was an influence of the attitude of officers with satisfaction of tuberculosis patients (p = 0.008), there is influence of perception of service procedure with tuberculosis patient satisfaction (p = 0.003), there is influence of perception of HR service with tuberculosis patient satisfaction (p = 0.002), there is no relationship between perception of drug service with tuberculosis patient satisfaction (p = 0.987), there is influence of facility perception with tuberculosis patient satisfaction (p = 0.002). The dominant variable related to tuberculosis patient satisfaction is the staff attitude variable (p = 0.003; OR = 5.4 CI95% 1,810-16,287) meaning that the attitude of officers who are not good has a risk of risk 5.4 times more patients are dissatisfied compared with the attitude of officers the good one.